The built environment and its impact on health outcomes and experiences of patients, significant others and staff-A protocol for a systematic review - Marie Elf; Anna Anåker; Elizabeth Marcheschi; Ásgeir Sigurjónsson; Roger S. Ulrich (Wiley, 2020)
Abstract Aim This review will identify, evaluate and synthesize the literature related to evidence‐based design of healthcare environments and to identify impacts of the built environment on the outcomes and experiences of patients, significant others and staff. Design A mixed‐method systematic review of literature 2010-2018. Methods Database searches for evidence in peer‐reviewed journals will be conducted electronically using CINAHL, Medline, SCOPUS and Web of Science. Abstract, full‐text screening and data extraction will be completed independently by the reviewers. Quality assessment will follow Swedish Agency for Health Technology Assessment and Social Services Assessment. Results This review will offer knowledge for informed decisions about the design of the healthcare environment. The review is comprehensive, includes a large volume of literature various research designs and will highlight the knowledge gap in evidence‐based design and provide a breadth of knowledge about the built environments and its impact on health and well‐being.